2021
DOI: 10.1029/2021ms002483
|View full text |Cite
|
Sign up to set email alerts
|

A Limited Area Modeling Capability for the Finite‐Volume Cubed‐Sphere (FV3) Dynamical Core and Comparison With a Global Two‐Way Nest

Abstract:  A limited area modeling capability has been developed for the FV3 dynamical core.  This capability was evaluated for a month-long period against a similarly configured twoway nest driven by a global model.  The limited area model is statistically comparable to the two-way nest for the first 24 hours, with minor degradation by 48-60 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The NWP module is built upon the Unified Forecast System Short-Range Weather (UFS-SRW) application version 1.0.0, which was first released in March 2021 [40]. The application includes a pre-processing utility, the FV3 Limited Area Model (LAM) [41], the Common Community Physics Package (CCPP) [42], and the Unified Post Processor (UPP). Already been chosen as the forecast module for NOAA's next-generation Rapid Refresh Forecast System (RRFS), performance evaluation studies have revealed its functionality and accuracy [43][44].…”
Section: Nwp Modulementioning
confidence: 99%
“…The NWP module is built upon the Unified Forecast System Short-Range Weather (UFS-SRW) application version 1.0.0, which was first released in March 2021 [40]. The application includes a pre-processing utility, the FV3 Limited Area Model (LAM) [41], the Common Community Physics Package (CCPP) [42], and the Unified Post Processor (UPP). Already been chosen as the forecast module for NOAA's next-generation Rapid Refresh Forecast System (RRFS), performance evaluation studies have revealed its functionality and accuracy [43][44].…”
Section: Nwp Modulementioning
confidence: 99%
“…Although JEDI also supports the limited area model version of FV3 (FV3‐LAM, Black et al., 2021), capabilities to assimilate regional data sets within JEDI for regional applications are still limited. No paper has been formally published testing and evaluating JEDI with FV3‐LAM according to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The National Centers for Environmental Prediction (NCEP) is currently developing the Rapid Refresh Forecast System (RRFS; Carley et al., 2021) as part of an effort to unify the NCEP operational forecast modeling systems using the finite volume cubed sphere (FV3; Putman & Lin, 2007) dynamical core. The RRFS is planned to run at a convection‐allowing grid spacing of 3 km using the FV3 limited area model (LAM; Black et al., 2021). The RRFS will replace current NCEP operational convection‐allowing model (CAM) systems that are based on the Weather Research and Forecasting (WRF; Skamarock et al., 2008) and Nonhydrostatic Multiscale Model on the B‐grid (Janjić & Gall, 2012; Janjić et al., 2001) dynamic cores which have been extensively evaluated, developed and tuned as a CAM over the years (e.g., Aligo et al., 2018; Clark et al., 2015; Grasso et al., 2014; Johnson & Wang, 2017, 2019; Johnson, Wang, Xue, & Kong, 2011; Kain et al., 2008; Weisman et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…at a convection-allowing grid spacing of 3 km using the FV3 limited area model (LAM; Black et al, 2021). The RRFS will replace current NCEP operational convection-allowing model (CAM) systems that are based on the Weather Research and Forecasting (WRF; Skamarock et al, 2008) and Nonhydrostatic Multiscale Model on the B-grid (Janjić & Gall, 2012;Janjić et al, 2001) dynamic cores which have been extensively evaluated, developed and tuned as a CAM over the years (e.g., Aligo et al, 2018;Clark et al, 2015;Grasso et al, 2014;Johnson & Wang, 2017, 2019Kain et al, 2008;Weisman et al, 2008).…”
mentioning
confidence: 99%